IMPLEMENTASI PENDIDIKAN AKHLAK ANAK SEKOLAH DASAR DALAM KELUARGA MENURUT PERSPEKTIF ISLAM - Siti Umayyah; Hanifah Fitriyani; Nanda Fairuz Fatin; Maura Febriyanti Zulkarnain (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Moral education is the foundational pillar in the sustainable development of a child’s character. From an Islamic perspective, the family plays a crucial role as the first and foremost institution responsible for instilling moral and ethical values. This study aims to understand how moral education is implemented within the family environment according to Islamic teachings, as well as to identify effective strategies that parents can apply. This research employs a descriptive qualitative method through a literature review approach. Data were collected from various sources, including books, academic journals, articles, and official documents relevant to the topic, and then analyzed thematically. The findings indicate that moral education in the family can be implemented through five main methods: exemplary behavior (uswah hasanah), habituation (ta’dib), advice and dialogue (mau’izhah), supervision (riqābah), and educational discipline (taqwīm). Each of these methods is strongly rooted in Islamic teachings, as derived from the Qur’an, Hadith, and the thoughts of scholars such as Imam Al-Ghazali. The study also shows that active parental involvement, effective communication, and exemplary daily behavior significantly influence the development of children’s moral character. Early moral education is essential in shaping a generation that is not only intellectually capable but also morally upright. Therefore, the family must serve as the primary agent in implementing moral education aligned with Islamic values.